PENGARUH KINERJA KEUANGAN TERHADAP KEBIJAKAN DIVIDEN DI BURSA EFEK INDONESIA - Aggy Eka Ressy; Anis Chariri (Diponegoro Journal of Accounting, 2013)
Dividend is earns or share half of profit which given to shareholders. Dividend payment paid in cash form or stock form which usually published every quartal. The amount of paid dividend for stakeholders depends on how come the dividend policy on their own firms. To determine dividend policy, corporations should consider factors which influencing dividend policy. The aim of this research is to know how much profitability, cash flow, firm size, firm growth and debt policy impact on dividend policy. This research used secondary data, which is annual financial report of companies which listed in Indonesian Stock Exchange per 2011. Researcher used purposive sampling to collect samples and used multiple regression to analyzed the data. Results of this research showed that profitability has positive impact on dividend policy. While cash flow, firm size, firm growth and debt policy has no impact on dividend policy.